It Is Not Just the Climate That Is Changing: Climate-Adaptive Development in Koh Kong, Cambodia - Horlings, Jason (Université d'Ottawa / University of Ottawa, 2017)
Developing countries must concurrently develop while also adapting to climate change; if not, the challenges of poverty alleviation are likely exacerbated. One response has been an emergence of literature emphasizing various approaches that address climate adaptation and development. There are approaches that focus on: climate-specific impacts, addressing underlying vulnerability of households or the resiliency of systems. Taken separately, these approaches have significant weaknesses, but a combined assessment of general and climate specific capacities at system and household scales, the adaptive development capacities framework, is promising. This framework is captured in a matrix that illustrates the presence of these capacities and thereby provides a basis for considering the relative importance and the interaction of climate-specific and general capacities at multiple scales. The framework has the potential to provide a nuanced, yet clear understanding of the extent that climate-adaptive development is occurring. This is important because there is a weak understanding of the interaction and relative importance of adaptive development capacities at multiple scales in developing countries. This thesis research sets out to operationalize the adaptive development framework (Eakin, Lemos and Nelson 2014) (when the research began, this framework had not yet been operationalized). This qualitative research project addresses this gap by focusing on coastal Cambodia. Cambodia is actively pursuing economic development through a range of policies, including developing a series of Special Economic Zones. For example, my case focuses on a Special Economic Zone (SEZ) located near the Thai border (between the border and a secondary coastal city, known as Koh Kong town) that began employing thousands of workers in 2012. At the same-time, Cambodia has ambitious climate adaptation policies, that include a coastal focus. Since the climate-adaptation and development effects of the SEZ, specifically its employment, are unknown, this case provides a strong setting for testing the adaptive development capacities framework. In this way, the SEZ is a window into better understanding the presence and interaction of adaptive development capacities across household and system scales. This thesis begins by introducing the research topic, research questions and adaptive development framework. The research methods are clearly detailed, before turning to an understanding of climate change within the context of broader environmental change in Koh Kong. Fisheries decline, coastal erosion and drinking water shortages are being driven by a series of drivers including off-shore fishing, sand-mining, mangrove loss, and urban growth in the coastal area, and these drivers are being exacerbated by the increasing effects of climate change in Koh Kong. Climate change risks include sea-level rise, increasing drought and more extreme and frequent storms. Turning to the adaptive development capacity of systems, this research uncovered no climate-specific capacities in Koh Kong’s industrial, urban and migration systems. Most problematically, the city is being developed without consideration of the climate change risks posed by sea-level rise and increased drought. This has already led to seasonal piped water shortages as the water demand pressures of factories, population growth, along with prolonged dry seasons, leads to insufficient water. The uneven quality of urban systems, and the variation in climate exposure, means that the residential location of households contributes to varying degrees of household adaptive development capacity. Although these systems lack climate-specific capacity, there is a high level of development capacity in the industrial system due to relatively high and predictable wages and a good working environment in this particular SEZ, in comparison to elsewhere in Cambodia. Linked to the strength of the SEZ as an employer, households – particularly those with females between 18-25 –are able to temporarily diversify or compliment their livelihoods from climate-exposed fisheries and farming towards the higher and more predictable wages of SEZ employment where there is minimal climate exposure. This means that although the Koh Kong’s systems lack specific climate adaptive capacity, households are able to use their agency to move towards a greater degree of adaptive development. However, not all households are able to achieve the same degree of climate adaptive capacity, and the timing of such adaptive capacity is very specific (the SEZ only hires women between 18-25). While local fishing households are optimally placed to take advantage of the proximity of the SEZ and their surplus female labour, migrant farming households face the higher costs of migration and greater female labour opportunity costs. Looking within households, the very high rate of female employment at the SEZ means that adaptive development is uneven across households. While the strengthening of household adaptive development capacity through time-sensitive SEZ employment is encouraging, in the long-term, the lack of adaptive capacity in Koh Kong’s systems could significantly limit or undermine these gains. Of concern is the pressure that industrialization, urban growth and migration are placing on Koh Kong’s urban water system, land-use practices and planning processes that are not able to address current environmental concerns, nor climate change risks. This creates the conditions for emerging vulnerabilities, and demonstrates the limits of household adaptive development capacity. These findings demonstrate the value of the adaptive development framework in articulating the forms and scales of capacity needed for adaptive development.
Keywords: Climate Change; Adaptation; Adaptive Capacity; Cambodia; Livelihoods; Special Economic Zones